Children Vaccination Reminder System via SMS Alert - Almohamed, Asam Hamed Abbas (2012)
This report presents a model for children vaccination reminder using short message service (SMS) to remind parents of the vaccination schedule. Vaccination is required to keep the children healthy and away from infections. In this report the main objective is to develop a children vaccination reminder model that operates via SMS. The general design methodology is the design used in this study and is represented using Unify model language (UML). The system is evaluated using questionnaires which were answered by parents. A percentage of 54.8 percent and 45.2 percent answered useful and very useful respectively of the proposed model. As a conclusion it is found that users do agree on the benefit of having reminder for their children vaccination appointment.